Disturbance alters ecosystem engineering by a canopy-forming alga. (23rd January 2017) - Pocklington, Jacqueline B.; Jenkins, Stuart R.; Bellgrove, Alecia; Keough, Michael J.; O'Hara, Tim D.; Masterson-Algar, Patricia E.; Hawkins, Stephen J.
Abstract : Canopy-forming fucoid algae have an important role as ecosystem engineers on rocky intertidal shores, where they increase the abundance of species otherwise limited by exposure during low tide. The facilitative relationship between Ascophyllum nodosum and associated organisms was explored using a frond breakage experiment (100%, 50%, 25%, 0% intact-frond treatments) in southern England, to assess the consequences of disturbance. Understorey substratum temperature was on average 3°C higher in 0% and 25% intact-frond treatments than in plots with 50% and 100% intact fronds. Light (as PAR during low tide) doubled in 0% intact-frond treatments in comparison to other treatments (which had similar light levels). Mobile invertebrate species richness declined by on average 1 species per m 2 in the treatments with only 25% and 0% intact fronds, and the abundance of Littorina obtusata declined by 2.4–4.2 individuals per m 2 in the treatments with 25 and 0% intact fronds. Sessile taxa, including Osmundea pinnatifida and encrusting coralline algae, declined by half on average in the 0% intact-frond treatment. These results suggest that the ability of Ascophyllum to mediate environmental conditions to the understorey is the mechanism responsible for species distributed in the understorey (autogenic ecosystem engineering). The results of this study imply that a pulse disturbance resulting in a 50% breakage of Ascophyllum fronds significantly increases temperature and decreases the abundance of mobile invertebrates usually associated with Ascophyllum . Sessile taxa associated with Ascophyllum can, however, withstand disturbances down to 25% intact Ascophyllum fronds.